FLOW PATTERN CHARACTERISTIC ANALYSIS OF PT. NEWMONT NUSA TENGGARA TAILING SLURRY DUE TO SEA PIPE SIZE DECREASING - ADAM PRATOMO (NIM : 12506008),
Based on Environmental Minister Regulation No.236 year 2007 that valid until May 2011, one condition that regulated in agreement of PT. NNT’s tailing locating in deep sea was minimum % solid tailing must be 25 %. One of recommendations that had been mentioned by the PSI (Pipeline System Incoorporated) was to increase tailing % solid by decreasing the size diameter of sea pipe (HDPE). That could be happened by pay attention to the characteristic of pipe that will be used and also the slurry flow behaviour that formed. The study was conducted to analyze and predict the flow patterns formed by slurry pipe diameter size reduction (HDPE). Flow patterns was predicted by CFD software by inputting data according to data obtained from PT. NNT. In this study, the diameter of pipe varied between 48 – 34 inches, variation in tonnage of 76 – 128 ktpd, and variation in reducer size between 1-2 meter long. The simulation results were then used to predict the patterns of velocity at the outlet pipe, the velocity patterns on the reducer wall of outlet pipe, and the velocity patterns along the 6 o’clock direction. From the simulation results could be deduced that the higher the tonnage the more the outlet velocity increases. The highest outlet velocity at the 128 ktpd is 12.55 m/s and the lowest outlet velocity at 76 ktpd is 10.7 m/s. Smaller diameter of the pipe outlet would increase the outlet pipe velocity. The highest velocity of the outlet pipe at 34 inch pipe was 12.55 m/s and the lowest velocity at 42 inch pipe was 7.2 m/s. The shorter the reducer size, the higher the outlet velocity. The highest outlet velocity at the one meter long reducer was 11.9 m/s, and the lowest outlet velocity at the two meter long reducer was 11.4 m/s. At the 6 o’clock direction for tonnage of 128 ktpd, the lowest velocity of inlet reducer was 3.07 m/s, and the highest velocity of outlet reducer was 10.31 m/s. At the same direction for the 34 inch outlet pipe, the lowest velocity of inlet reducer was 3.25 m/s and the highest velocity of outlet reducer was 9.88 m/s. Still at the 6 o’clock direction for one meter long reducer, the lowest velocity of inlet reducer is 3.25 m/s, and the highest velocity of outlet reducer is 9.88 m/s.